Collective intermittent exploration in fish schools is mediated by visual cues - Deze Liu; Daniel Burbano (Royal Society Open Science, 2025)
Exploratory behaviour is fundamental to animal collectives, directly influencing fitness through resource acquisition and predator avoidance. Despite its ecological significance, the processes governing when and how animals initiate exploration in social contexts under varying sensory inputs remain poorly understood. Here, we investigate how the number of individuals and illumination (modulating visual input) influence zebrafish exploratory behaviour. Visual cues were quantified via opacity (field occupancy) and optic flow (relative motion). With visual input, zebrafish exhibited higher swimming activity and shorter exploratory bursts, while its absence led to more dispersed and prolonged exploration. Interestingly, fish triads without visual input exhibited longer exploration times compared to dyads. A data-driven stochastic model revealed a bistable potential landscape balancing social cohesion and exploration, modulated by a parabolic noise term driving decision-making. Visual cues biased the potential towards conspecific proximity, while their absence diminished this effect, promoting prolonged exploration. The noise term follows an entropy-like pattern analogous to a coin flip, reaching maximal uncertainty at intermediate distances and forcing individuals to break indecision between proximity and exploration. These findings point to a complex interplay between sensory input and group dynamics, underscoring the profound impact of environmental changes and the number of conspecifics on collective behaviour.